ACADEMIC BUOYANCY: EXPLORING LEARNERS' EVERYDAY RESILIENCE IN THE LANGUAGE CLASSROOM. Issue 4 (16th April 2018) - Yun, Saerom; Hiver, Phil; Al-Hoorie, Ali H.
Abstract: This article reports the first attempt to test the relevance of buoyancy—the capacity to overcome the setbacks, challenges, and pressures that are part of the ordinary course of school life—for instructed second language (L2) learning. Questionnaire data from 787 college-level L2 learners in South Korea assessed their academic buoyancy and a set of six hypothesized predictors. A two-step cluster analysis of the data identified five prominent L2 learner archetypes, providing evidence for the existence of L2 domain-specific buoyancy profiles. Using structural equation modeling, we examined links among the six predictor variables, buoyancy, and L2 achievement and grade point average (GPA). The results showed that buoyancy significantly predicted both L2 achievement and GPA and mediated the effect of the predictors on these two outcome variables. Buoyancy, thus, captures a dimension of L2 motivation that is conceptually and empirically distinct from existing constructs, and represents an essential yet underexplored capacity for success in language learning.